DOMESTIC TOURISM IN GEORGIA: QUANTITATIVE ANALYSIS - Nino Jerenashvili (European Scientific Journal, ESJ, 2014)
Domestic tourism is an interesting direction. On the one hand, domestic tourism is the important part of the country economy, because, as it is known, domestic tourists spend money in their own country, as a result there is flow of money. On the other hand, domestic tourism plays an important role in the development of the regions of the country which does not have manufacturing resources and facilities. Therefore, for developing the domestic tourism and not only, also for growing the international tourists flow, it is very important to grow the awareness of the country as in the local population, also on international markets. In most cases, domestic tourists have demand on the same products that demand international ones. Domestic tourists use the infrastructure and objects which are designated for local population. The proper development of the domestic tourism will assist promotion and position strengthening of Georgian tourist product on the country’s target touristic markets.